Long and Short-term Investments by European Banks – Trends Since the IASB Published IFRS 9 - Edgar Löw; Marc Erkelenz (Australian Accounting Review, 2022)
IFRS 9 was introduced by the IASB in 2014 with a mandatory application in 2018. Three years later the IASB started a post-implementation review project. Major concerns at a political level and from the (insurance) industry were raised about long-term investment strategies that appear less favourable due to new measurement categories and impairment rules. Furthermore, it was expected that the new rules on categorisation would create more profit or loss (P/L) volatility. We show that concerns about banks' decreasing maturity investment behaviour and increased profit or loss volatility since the publication of IFRS 9 in 2014 could not be verified until 2020. Additionally, banks hardly use the fair value option in practice, which suggests it can be abolished. Finally, the paper finds that the fair value through other comprehensive income option for equity instruments has almost no importance for banks. The IASB should, therefore, abolish this category as well. Hence, the measurement categories could be reduced by two categories reducing complexity and increasing the decision usefulness of financial instruments accounting rules for investors.
Keywords: 650